Educação ambiental na contemporaneidade: a constituição de um ethos ambiental - Kuhnen, Claudia Felin Cerutti (Universidade do Vale do Rio dos Sinos, 2020)
This doctoral dissertation analyzes the way that educative practices carried out by the Culture Caravan Project in Defense of Sustainability and Environment functioned in the triad established between Community, School and University for the constitution of environmental education (EE) in the region addressed by the Intercity Consortium of Solid Waste Management. The guiding questions of this research have been the following: Which educative practices for environmental education did the Caravan Project develop? How did the EE educative practices developed in the triad function in the Caravan Project? How did the educative practices of the Caravan Project affect EE in the region? The concepts of environmental experience and educative practices were used in the qualitative analysis of the Caravan Project, whose educative practices were mapped. Regarding the design, execution and follow-up of the environmental actions of the Caravan Project, there was an attempt to find out how those educative practices were developed in the triad. The empirical material of this study consisted of: Public Notice/Project; 10 follow-up reports of the Caravan Project and their respective attachments; and the handbook Environmental Education: Solid waste and selective garbage collection. The analysis has enabled the understanding of environmental education in different loci, such as School, Community and University. The triad, grounded on the very structure of the Project, still needs to be strengthened and managed in a more contextualized way, together with the needs and challenges of Contemporaneity in different sectors of the cities participating in the Project. The way that the educative practices have functioned in those settings, the environmental experience and the constitution of an environmental ethos are still fragile and inoperative in some sectors. It has been possible to identify great difficulties, such as discontinuity of projects and actions, and lack of municipal public policies to guide and support both the constitution and permanence of an environmental ethos, and develop educative practices as environmental experience. The thesis I have defended is that environmental education should focus on educative practices that enable the environmental experience, in order to create an environmental ethos by gathering subjects around new ways of being and acting in relation to the environment, by involving the social-environmental co-responsibility and the sustainability of the planet, especially of human beings.
Keywords: Educação ambiental; Práticas formativas; Ethos ambiental; Projeto ambiental; Environmental education; Educative practices; Environmental ethos; Environmental project; ACCNPQ::Ciências Humanas::Educação